Immunization with chlamydial type III secretion antigens reduces vaginal shedding and prevents fallopian tube pathology following live C. muridarum challenge. Issue 34 (25th July 2016) - Bulir, David C.; Liang, Steven; Lee, Amanda; Chong, Sylvia; Simms, Elizabeth; Stone, Christopher; Kaushic, Charu; Ashkar, Ali; Mahony, James B.
Abstract: Chlamydia trachomatis infections in women are often asymptomatic and if left untreated can lead to significant late sequelae including pelvic inflammatory disease and tubal factor infertility. Vaccine development efforts over the past three decades have been unproductive and there is no vaccine approved for use in humans. The existence of serologically distinct strains or serovars of C. trachomatis mandates a vaccine that will provide protection against multiple serovars. Chlamydia spp. use a highly conserved type III secretion system (T3SS) composed of both structural and effector proteins which is an essential virulence factor for infection and intracellular replication. In this study we evaluated a novel fusion protein antigen (BD584) which consists of three T3SS proteins from C. trachomatis (CopB, CopD, and CT584) as a potential chlamydial vaccine candidate. Intranasal immunization with BD584 elicited serum neutralizing antibodies that inhibited C. trachomatis infection in vitro . Following intravaginal challenge with C. muridarum, immunized mice had a 95% reduction in chlamydial shedding from the vagina at the peak of infection and cleared the infection sooner than control mice. Immunization with BD584 also reduced the rate of hydrosalpinx by 87.5% compared to control mice. Together, these results suggest that highly conserved proteins of the chlamydial T3SS may represent good candidates for a Chlamydia vaccine.